Improving efficiency for ensuring data group anonymity by developing an information technology - Chertov, Oleg; Tavrov, Dan (Eastern-European Journal of Enterprise Technologies, 2018)
Widespread introduction of methods that ensure anonymity of information about individual groups (teams) of respondents in the field of official statistics is restrained by the lack of relevant industrial information technologies and systems. A three-level client-server architecture of an information technology providing data group anonymity was provided in which clients, application servers and databases are united into a local network to enhance security of primary data. A conceptual data model covering all key components of group anonymity was described. Implementation of the technology based on the Java Enterprise Edition 8 platform, Oracle GlassFish Server application server, MySQL database server and SciLab engineering calculations system wase considered. The information technology enables provision of group anonymity of data in the event of a threat of its violation by analyzing data of an auxiliary microfile. The technology provides operations for constructing fuzzy group models using a genetic algorithm and modification of a microfile with the help of a mimetic algorithm which enables effective provision of anonymity by introducing minor insignificant distortions into data. Application of the technology was illustrated by solution of the task of providing anonymity of a military group based on real data of American Society Survey, 2013. It was shown that solving the problem by a team of five specialists has enabled at least two and a half times faster the process of preparation of a microfile than by the use of an existing technology